A retrospective comparison of the biceps femoris long head muscle structure in athletes with and without hamstring strain injury history - Yagiz, G.; Fredianto, M.; Ulfa, M.; Ariani, I.; Agustin, A. D.; Shida, N.; Moore, E. W. G.; Kubis, H. P. (PLOS ONE, 2024)
Introduction Hamstring strain injuries (HSI) and re-injuries are endemic in high-speed running sports. The biceps femoris long head (BFlh) is the most frequently injured muscle among the hamstrings. Structural parameters of the hamstring muscle are stated to be susceptible to strain injuries at this location. This retrospective study targeted comparing the BFlh`s structural parameters between previously injured and uninjured athletes.